MANIFESTASI PANGADERENG BERBASIS TODDO’PULI TEMMALARA’ PADA MAHASISWA PGSD UNIVERSITAS COKROAMINOTO PALOPO - Andi Kilawati (Universitas Trilogi, 2020)
Abstract:This study discusses the fatherly-based manifestation of 'puli' temmalara on PGSD students at Cokoroaminoto Palopo University. Data used in the discussion of this study were collected through the performance of the Bugis cultural festival related to toddo 'puli temmalara. Pangadereng based on toddo 'puli temmalara is the actualization of civilization to not back down a step from the struggle in maintaining dignity and dignity. Pangradeng based on toddo puli temmalara which is actualized at PGSD students will hold a cultural festival related to everyday life to traditional rituals. Character valuesembodied in this pangadereng are; (a) truth / tongeng, (b) honesty / slab, (c) fair / adele, (d) getteng (firmness). Pangadereng (Civilization) based on toddo puli temmalara is very important for the community, both at the local, national and global level.